High‐density stacking faults in a supersaturated nitrided layer on austenitic stainless steel. Issue 6 (27th October 2016) - Tong, Ke; Ye, Fei; Che, Honglong; Lei, Ming Kai; Miao, Shu; Zhang, Chi
Abstract : Dense stacking faults in a supersaturated nitrided layer produced on austenitic stainless steel were systematically investigated by transmission electron microscopy, and then a novel microstructure model of clustered stacking faults embedded in a face‐centred cubic structure was built. Abstract : The nitrogen‐supersaturated phase produced by low‐temperature plasma‐assisted nitriding of austenitic stainless steel usually contains a high density of stacking faults. However, the stacking fault density observed in previous studies was considerably lower than that determined by fitting the X‐ray diffraction pattern. In this work, it has been confirmed by high‐resolution transmission electron microscopy that the strip‐shaped regions of about 3–25 nm in width observed at relatively low magnification essentially consist of a series of stacking faults on every second 111 atomic plane. A microstructure model of the clustered stacking faults embedded in a face‐centred cubic structure was built for these regions. The simulated X‐ray diffraction and transmission electron microscopy results based on this model are consistent with the observations.